Penguatan Sikap Moderat dalam Keberagaman Etnik di Madrasah Aliyah An-Nur Trisono Babadan - Nisa', Khoirotun; Swara, Kinarsih Nanda Sekar; Kurniasari, Kurniasari; Kamila, Lia Alfi; Astuti, Linda Nur Fitria; Safrudin, Lutfiah Firdaus (Rausyan Fikri Journal of Islamic Studies, 2023)
Madrasah Aliyah is a formal Islamic educational institution in Indonesia at the secondary education level under the management of the Ministry of Religion. The bad stigma of the community about Madrasah students who think radically in understanding religious teachings needs to be counteracted by providing an understanding of religious moderation to students and the role of instilling this understanding is the teacher. The purpose of this research is to find out the strategic steps taken by the teachers of MA An-Nuur in strengthening moderate Islam for their students and to find out the extent to which students from MA An-Nuur understand moderate Islam. Researchers are directly involved in the research process by using a qualitative approach method and using observation and interview techniques in collecting information and data so that the information and data that has been collected is accurate and in accordance with the needs of researchers. Based on the research results, it is known that the understanding of teachers and students of MA An-Nuur regarding moderation is an attitude that represents fairness, mutual respect and tolerance. And the result of the implementation of strengthening the attitude of moderation to students of MA An-Nuur is in the form of an attitude that respects ethnic and racial differences.